PENERAPAN DIVERSI TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM PADA TINGKAT PENUNTUTAN DI KEJAKSAAN NEGERI PONTIANAK - NIM. A1011201168, MEILANI (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract A child in conflict with the law may have a better chance of achieving psychological recovery through reintegration into society, which is more easily accomplished compared to when a child has already faced imprisonment. This is related to the negative stigma imposed by society, which implicitly might occur when a child has been criminally sentenced. This research employs empirical research methods. The data source for this study is derived from primary data obtained through interviews with Public Prosecutors at the State Attorney's Office in Pontianak, while secondary data is sourced from literature and relevant legal regulations. In practice, the implementation of Diversion in the State Attorney's Office in Pontianak for juvenile offenders is largely unsuccessful. The obstacles in the implementation of the Diversion process at the State Attorney's Office in Pontianak include the community's lack of understanding of the objectives and functions of Diversion for the future of the child. Keywords: Public Prosecutor